Emprendimiento transgeneracional en la empresa familiar: factor clave para la competitividad de las MIPYMES - Pérez Espinoza, María José (2018)
To last with success inthe time, is one of the main objectives of all enterprise, and even more important in the family companies. The longevity depends mainly in the entrepreneur capacity of the business family, generation after generation. This capacity allows that the familybusiness develops values, and generates resources and capacities in the family members that let them to develop new business ideas, new products that create social and financial value and in that way to reach a competitive advantage in the time. The competitiveness is a term that is closely related with the enterprises indifferently of their sizes. Certainly, the principal source of business creation is responsibility of the entrepreneurs that daily take the risk to immerse in the adventure to start a company taking into account the small identified needs, mainly in family businesses, that according to statistical sources represent more than 80% of the companies that are part of the economic sector. The objective of this research is to present a complete and objective analysis about the relationship between the competitiveness, the entrepreneurship and its presence and influence in the companies mainly in those who are considered as familiar that reach to be transgenerational justly for the timely identification of new market niches, business lines or innovations to the traditional family enterprise.